ANALISIS PENGARUH DIKLAT DAN MOTIVASI TERHADAP KINERJA DANKAR : ANALYSIS OF THE EFFECT OF TRAINING AND MOTIVATION ON DANKAR'S PERFORMANCE - Agus Sugeng Setiawan; Heri Sasono (Lembaga Pengembangan Kinerja Dosen, 2022)
Education, training and motivation greatly affect the performance of employees of an organization. The purpose of this study was to analyze the effect of education, training and motivation on the performance of the Fire and Rescue Service Sub-dept. of Sector 2, Palmerah District, West Jakarta. The research population was 80 people and the research sample, that is, all the population was used as the research sample (census). The analysis method uses correlation, determinant coefficient, multiple linear regression analysis, t test, F test (Anova) with SPSS software. The results of the study were only education which had no significant effect, while training and motivation had a significant effect on employee performance, while simultaneously had a significant effect on the performance of the Fire Service Sub-dept. Linear Regression Analysis Y = 0.617 + 0.150 X1 + 0.222 X2 + 0.158 X3 and the determinant coefficient is 80.1%.